2022
DOI: 10.1016/j.euf.2021.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiotherapy After Radical Cystectomy for Patients with High-risk Muscle-invasive Bladder Cancer: Results of a Multicentric Phase II Trial

Abstract: Background: High-risk muscle-invasive bladder cancer (MIBC) has a poor prognosis. Old trials showed that external beam radiotherapy (EBRT) after radical cystectomy (RC) decreases the incidence of local recurrences but induces severe toxicity. Objective: To evaluate the toxicity and local control rate after adjuvant EBRT after RC delivered with volumetric arc radiotherapy. Design, setting, and participants: This is a multicentric phase 2 trial. From August 2014 till October 2020, we treated 72 high-risk MIBC pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…Simultaneous integrated boost (SIB) of up to 70 Gy was delivered to suspicious lymph nodes detected in 18F-FDG-PET-CT. The study suggested that adjuvant RT resulted in good LC and acceptable toxicity (Fonteyne et al, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…Simultaneous integrated boost (SIB) of up to 70 Gy was delivered to suspicious lymph nodes detected in 18F-FDG-PET-CT. The study suggested that adjuvant RT resulted in good LC and acceptable toxicity (Fonteyne et al, 2021).…”
Section: Introductionmentioning
confidence: 93%
“…Between August 2014 and October 2020, 72 patients with MIBC were treated with ART after RC within a Belgian prospective phase 2 trial. 7 Within this trial, all patients received elective pelvic nodal irradiation using intensity modulated arc therapy. The lymph node areas located along the common, internal and external iliac artery, obturator fossa, and presacral were delineated.…”
Section: Phase 2: Pattern Of Failure Analysismentioning
confidence: 99%
“…5 These trials suggested that ART is safe and effective. 6,7 To guide the contouring of the clinical target volume (CTV) for ART in these high-risk MIBC patients after RC, in 2016, international consensus CTV (CTV-IC-2016) guidelines were published by Baumann et al 8 After external validation, Reddy et al 9 proposed an optimized CTV (CTV-OPT). The aim of this study was to develop updated international consensus CTV guidelines by evaluating the current contouring practice that makes use of existing guidelines and the locoregional ART results.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with muscle‐invasive bladder cancer who are ineligible for cisplatin chemotherapy, upfront radical cystectomy is the preferred treatment paradigm 12 . Adjuvant chemotherapy (if not treated with neoadjuvant chemotherapy before) or the immunotherapeutic agent nivolumab (anti‐ T‐cell PD‐1 receptor), which is often prescribed for patients with high risk for cancer recurrence after cystectomy 13,14 …”
Section: Introductionmentioning
confidence: 99%
“…12 Adjuvant chemotherapy (if not treated with neoadjuvant chemotherapy before) or the immunotherapeutic agent nivolumab (anti-T-cell PD-1 receptor), which is often prescribed for patients with high risk for cancer recurrence after cystectomy. 13,14 Patients with inoperable or metastatic BC are usually treated with palliative, multiagent platinum-based chemotherapy. 9 If there is no cancer progression after chemotherapy, avelumab (anti-PDL-1 on tumor cells) maintenance therapy is the standard of care.…”
Section: Introductionmentioning
confidence: 99%